HUBUNGAN MEROKOK DENGAN KEJADIAN GASTRITIS DI WILAYAH KERJA PUSKESMAS TRUCUK KECAMATAN TRUCUK KABUPATEN BOJONEGORO TAHUN 2022: THE CORRELATION OF SMOKING WITH GASTRITIS INCIDENCE IN THE WORK AREA OF TRUCUK HEALTH CENTER TRUCUK DISTRICT, BOJONEGORO REGENCY - Patonah, Siti; Susanti, Dwi Agung; Kusuma Dewi, Dyah Savitri (WELL BEING, 2023)
Gastritis sufferers at the Trucuk Health Center do not practice clean and healthy lifestyles to stop smoking because of addiction. The purpose of the study was to determine the correlation between smoking and the incidence of gastritis at the Trucuk Health Center in 2022. The type of research used is ex post facto with a causal research approach. The population of all gastritis patients May 2022 amounted 91 people. The sampling used is non-probability sampling by purposive sampling with a sample of 33 people. Collecting data using questionnaires and medical records. Then analysis using Chi Square statistic and Crosstable statistic. The results showed that at the level of significance = 0.05 with a value of (p) = 0.001. So that it is H0 rejected and H1 is accepted and it can be concluded that there is a correlation between smoking and the incidence of gastritis at the Trucuk Public Health Center, Trucuk District, Bojonegoro Regency in 2022. Smoking habits affect the severity of the type of gastritis experienced. Therefore, it is expected that health workers, especially nurses, can provide counseling to gastritis sufferers to adhere to a healthy lifestyle that minimizes the occurrence of recurrences and complications of gastritis.